2018
DOI: 10.1111/nph.15507
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study reveals new loci involved in Arabidopsis thaliana and Turnip mosaic virus (TuMV) interactions in the field

Abstract: Summary The genetic architecture of plant response to viruses has often been studied in model nonnatural pathosystems under controlled conditions. There is an urgent need to elucidate the genetic architecture of the response to viruses in a natural setting. A field experiment was performed in each of two years. In total, 317 Arabidopsis thaliana accessions were inoculated with its natural Turnip mosaic virus (TuMV). The accessions were phenotyped for viral accumulation, frequency of infected plants, stem len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 77 publications
(104 reference statements)
3
52
4
Order By: Relevance
“…Here, we found that the ruderal character of an accession was positively related to its capacity to tolerate virus infection, and, to a lesser extent, water deficit. Considering the adaptive value of functional strategies across the natural diversity of A. thaliana [19,20,27,43], this result affirms the importance of investigating the role of phytoviruses as selective agents in natural populations of ruderal species [36,70,71].…”
Section: Plos Pathogenssupporting
confidence: 64%
“…Here, we found that the ruderal character of an accession was positively related to its capacity to tolerate virus infection, and, to a lesser extent, water deficit. Considering the adaptive value of functional strategies across the natural diversity of A. thaliana [19,20,27,43], this result affirms the importance of investigating the role of phytoviruses as selective agents in natural populations of ruderal species [36,70,71].…”
Section: Plos Pathogenssupporting
confidence: 64%
“…The cis-regulatory sequence bZIP, observed for the transcripts aligned to DTFs 5000_26 and 5000_34, along with the sequence TALE, associated with DTFs 5000_23, 5000_24, and 5000_25, further indicated the association with stress responses. For instance, the presence of stress-responsive bZIP transcription factor-binding site is in accordance with the annotations assigned to the sugarcane transcripts Sh_083B09_g000030 and Sh_213J23_g000110, respectively, reported as responsive to potyvirus infection and as an intermediate of intercellular movement of potyviruses [80,82]. Moreover, the cis-regulatory sequence TALE includes transcriptional activators of plant genes during pathogenesis [86], which indicates response to biotic stresses for the transcript Sh_005D21_g000060, assigned to molecular chaperones and protein quality control [83].…”
Section: Plos Onesupporting
confidence: 80%
“…The former was revealed by the alignment between DTF 5000_26 and transcript Sh_083B09_g000030, which is described as "similar to Organic cation transporter-like protein" and assigned to the pfam motifs described as "Oxidoreductase family, NAD-binding Rossmann fold." Similarly, oxidoreductases have been shown to be activated in Arabidopsis thaliana in response to turnip mosaic virus infection by a genome-wide association study [80]. Alignment with SYT proteins and the GO term "lipid transport" was observed for DTF 5000_34, which was downregulated according to cDNA-AFLP observations.…”
Section: Sequencing Of Dtfsmentioning
confidence: 93%
“…The RTM gene complex in Arabidopsis has been the focus of research for more than 20 years and prevents long-distance transport of potyviruses. The RTM genes convey dominant resistance to tobacco-etch potyvirus (TEV) [5,32], lettuce mosaic virus (LMV) and plum pox virus (PPV) [33], and may be associated with quantitative resistance to turnip mosaic virus (TuMV) [34]. Potato potyvirus Y (PVY), tobacco vein mottling virus (TVMV) and cucumber mosaic cucumovirus (CMV) do not seem to be affected by RTM-mediated resistance [5].…”
Section: Rtm-mediated Resistance To Potyvirusesmentioning
confidence: 99%